2022
DOI: 10.1055/a-1899-8233
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Mediated Heme Oxygenase-1 Activation Contributes to Diabetic Wound Healing – an Overview

Abstract: Diabetic wound healing is a complicated procedure because hyperglycemia changes the various stages of wound healing. In type 2 diabetes mellitus (T2DM), oxidative stress is proven to be a critical factor in causing non-healing wounds and aggravating the inflammatory phase, resulting in the amputation of lower limbs in T2DM patients. This makes scientists figure out how to control oxidative stress and chronic inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…31 Alterations of mitochondrial function and the increased ROS generation negatively impact recovery, maintaining the wound in a prolonged inflammatory phase, further impairing the healing process. 7,35 The overproduction of mtROS also contributes to impaired keratinocyte mitochondrial function under high glucose conditions. 15 Moreover, our previous work indicated that mitochondrial remodelling is important in skin wound healing progression and it is impaired under diabetic conditions, contributing to deficient wound healing in a preclinical diabetes mouse model.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…31 Alterations of mitochondrial function and the increased ROS generation negatively impact recovery, maintaining the wound in a prolonged inflammatory phase, further impairing the healing process. 7,35 The overproduction of mtROS also contributes to impaired keratinocyte mitochondrial function under high glucose conditions. 15 Moreover, our previous work indicated that mitochondrial remodelling is important in skin wound healing progression and it is impaired under diabetic conditions, contributing to deficient wound healing in a preclinical diabetes mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…5 In addition, high levels of reactive oxygen species (ROS) are also observed in wounds under diabetic conditions, 4,6 aggravating the inflammatory phase. 7 Therefore, much effort has been undertaken to understand the pathogenesis and repair wound healing under diabetes conditions, and to develop novel therapeutics targeting oxidative stress and inflammation, to treat DFUs. [6][7][8] Wound healing impairment is equally prevalent under either type one or type two diabetes, and the mechanisms of tissue repair involved are similar.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations